Assessment of Mapping Insecticide Resistance of Dengue Vectors in Northern Viet Nam From 2010-2021 - Tran Thanh Duong; Nguyen Quang Thieu; Bui Le Duy; Vu Duc Chinh; Nguyen Van Tuan; Nguyen Tran Bich Diep; Ho Dinh Trung; Nguyen Van Dung (New Visions in Biological Science Vol. 10, 2022)
The study determined the susceptibility and resistance of mosquito populations from 189 sites in 12 provinces/cities in Northern Vietnam using WHO standard procedures bioassay for susceptibility of mosquitoes to insecticides. The widespread insecticide resistance status of dengue vectors in Northern Vietnam was mapped from 2010 to 2021. The information was gathered in the provinces of Ha Noi, Quang Ninh, Vinh Phuc, Bac Ninh, Cao Bang, Lang Son, Nam Dinh, Thai Binh, Hai Phong, Thanh Hoa, Nghe An, and Ha Tinh, and is an update of documentation on the distribution and insecticide resistance status of dengue vectors in Northern Vietnam, particularly pyrethroid resistance status. Most of Ae. aegypti populations from Ha Noi city were resistant to alphacypermethrin, cyfluthrin, deltamethrin, etofenprox, lambdacyhalothrin, permethrin, and DDT, but susceptible to malathion; most of the populations in other sites of the North are tolerant. The majority of populations of Aedes albopictus in most studied sites in 12 Northern provinces of Vietnam were resistant to DDT but susceptible to alphacypermethrin, cyfluthrin, deltamethrin, permethrin, lambdacyhalothrin, and Malathion, with a few populations being tolerant. This document is targeting policy makers, national program managers, as well as all partners involved in dengue control in Viet Nam.